Strong interactions between Au nanoparticles and BiVO4 photoanode boosts hole extraction for photoelectrochemical water splitting - He, Bing (2024)
Strong metal-support interaction (SMSI) is widely proposed as a key factor in tuning catalytic performances. Herein, the classical SMSI between Au nanoparticles (NPs) and BiVO4 (BVO) supports (Au/BVO-SMSI) is discovered and used innovatively for photoelectrochemical (PEC) water splitting. Owing to the SMSI, the electrons transfer from V4+ to Au NPs, leading to the formation of electron-rich Au species (Auδ-) and strong electronic interaction (i.e., Auδ--Ov-V4+), which readily contributes to extract photogenerated holes and promote charge separation. Benefitted from the SMSI effect, the as-prepared Au/BVO-SMSI photoanode exhibits a superior photocurrent density of 6.25 mA cm-2 at 1.23 V versus the reversible hydrogen electrode after the deposition of FeOOH/NiOOH cocatalysts. This work provides a pioneering view for extending SMSI effect to bimetal oxide supports for PEC water splitting, and guides the interfacial electronic and geometric structure modulation of photoanodes consisting of metal NPs and reducible oxides for improved solar energy conversion efficiency.